1986
DOI: 10.1007/bf00046428
|View full text |Cite
|
Sign up to set email alerts
|

Interferons in the treatment of human papillomavirus diseases

Abstract: A variety of epithelioproliferative benign neoplasms, both trivial and life-threatening, are caused by subtypes of human papillomaviruses. Interferons objectively regress HPV-induced warty disease and affect the regrowth of the transformed epithelium. Interferons effectively control the most serious and potentially life-threatening papillomavirus associated diseases, respiratory papillomatosis and genital warts, but not without the anticipated side effects associated with this potent biological weapon. It is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The synthesis of 14 and related derivatives has recently been reviewed (62). Studies have-shown that DHPG, 10, is very effective in the treatment of herpetic corneal lesions in rabbits (63).…”
Section: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of 14 and related derivatives has recently been reviewed (62). Studies have-shown that DHPG, 10, is very effective in the treatment of herpetic corneal lesions in rabbits (63).…”
Section: Bmentioning
confidence: 99%
“…They are divided in established indications which are beyond doubt, and possible indications, for which the clinical significance remains to be proven. The viral infection in which interferon has led to the most dramatic response, is juvenile laryngeal papillomatosis (JLP) (63). It is a wartlike disease which occurs commonly around the vocal cords and leads to considerable morbidity and mortality, especially when the disease starts early in life.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After encountering promising results with interferon-~ therapy in a concomitant trial [5], we monitored its proficiency and conducted this comparative trial. Interferons are a group of lowmolecular weight (24-26 kDa) glycoproteins which act on cells to interfere with viral replication, thereby inhibiting the production of various RNA, DNA viruses including human papilloma viruses [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known to be associated with human Papillo mavirus (HPV) in approximately 90% of cases. IFNs have been demonstrated to induce regression of warts associat ed with HPV and to effectively treat other Papillomavi rus-related diseases such as respiratory papillomatosis [77] suggesting a strong rationale for their use in CIN.…”
Section: Cervical Cancer and Cervical Intraepithelial Neoplasiamentioning
confidence: 99%